The Role of Study Program In Political Education - Zuryani, Nazrina; Citra Ranteallo, Ikma; Kebayantini, Ni Luh Nyoman (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017, 2017)
Research grant/HUPS for Sociology Department from Udayana University utilized FGD to frame up the political education utilized by internship and learning via text book of ‘Political Parties Accountability’ published in 2015 at FISIP Unud that is compared with general lecture delivered by Nazrina Zuryani1) as guest lecturer at Bina Nusantara International (communication Department) in Jakarta. Bina Nusantara International University has not Faculty of Social and Political Sciences as in UNUD but all the students get double degree with overseas universities and Communication department belongs to Faculty of Computing and Media of Binus International. Political education at Sociology department of UNUD has not yet increase the critical thinking of students by argumentation while Binus International urge their students to be more critical for any social changes and global politics. Utilizing the organizational of political parties by Basedeau dan Stroh (2008), as well as the critics from Heywood (2013) who said that political parties have not yet successfully implementing politic of education for people especially the youth. This research is the result of comparing the political education that has been minor in critical thinking at Sociology department at Unud Bali but in contrary, it becomes a major critical thinking for global politics topic at Binus International in Jakarta. Both participants of Focus Group Discussion/FGD were 26 students and 21 students for general lecture. Almost 85% of FGD participants had undertaking subject of Political Sociology while participants of ‘Political Globalization’ never undertaking it. The result of FGD shows that most of students unaware of global politics as they focus only at subjects’ correlations while at Binus International, the general lecture participants shows the ability to synthesize the social and political engineering to face the dilemma of right wings that now are pandemic in the global world.